Syn-eruptive/inter-eruptive relations in the syn-rift deposits of the Precuyano Cycle, Sierra de Chacaico, Neuquén Basin, Argentina - Muravchik, Martin (2011)
The syn-rift volcanic successions of the Upper Triassic–Lower Jurassic Precuyano Cycle (i.e. the Lapa Formation) from the Sierra de Chacaico in the Neuquén Basin, Argentina, were studied in order to address the distinctive characteristics of accumulation during syn-eruptive and inter-eruptive periods in a depocentre associated with active volcanism and extensional tectonics. In particular, the syn-rift ﬁll in this area comprises a wide range of compositions, as well as of transport and depositional processes. Lava ﬂows coexist with pyroclastic and epiclastic deposits in the same accumulation space. In order to analyse the complexities inherent in a volcanic environment subjected to extension, ﬁve different accumulation units were identiﬁed in the area: Lava Flow/Shallow Intrusion Units, Pyroclastic Units, Volcaniclastic Alluvial Units, Polymictic Alluvial Units, and Lacustrine Units. The analysis of each of these units and of the relationship between them provided meaningful insights into the evolution of the syn-rift sedimentary environments and the identiﬁcation of different stages of effusive activity, explosive activity and relative quiescence, determining syn-eruptive and inter-eruptive rock units. The relationship between these units was examined, and two accumulation stages were deﬁned. The underﬁlled stage originates when the material supplied to the depocentre during the eruptive events is not enough to level the existent topography, allowing the development of high-gradient alluvial systems during the next inter-eruptive period. The overﬁlled stage occurs when extensive pyroclastic density current deposits choke the accumulation space during syneruptive periods, causing low-gradient sedimentary systems to develop during the subsequent inter-eruptive periods.